(untitled) (SCIENCE TIME JOURNAL, 2026)
This article investigates the cross-cultural pragmastylistic aspects of proverbs concerning labor in English and Uzbek. Proverbs are a significant component of national culture and linguistic perspectives, mirroring societal views on work, effort, accountability, and social principles. The study dissects the semantic, pragmatic, and stylistic traits of labor proverbs, noting their commonalities and divergences across both languages. English proverbs on labor primarily highlight individual achievement, time utilization, and output, whereas Uzbek proverbs concentrate on communal principles, perseverance, integrity, and esteem for diligent labor. The research further examines the communicative and expressive roles of proverbs in discourse.Comparative analysis demonstrates that labor proverbs serve as important linguistic tools for moral education and cultural transmission.